Modeling technology of large-scale half speed unit and its thermal actuator participating in grid frequency modulation. Issue 1 (February 2021) - Wen, Libin
Abstract: In view of the shortage of the technology of large half speed units in nuclear power participating in the primary frequency regulation modeling and parameter measurement of power grid, the speed regulation system, thermal actuator and prime mover model of nuclear power unit are established. At the same time, the technology of model parameter test, identification and verification is developed. The developed technology meets the requirements of BPA. Through the frequency step simulation of the established model and the obtained model parameters, and compared with the field test results, the results show that the model and its parameter test method are correct. The established model and its parameters can accurately reflect the dynamic process of nuclear motor group participating in the primary frequency modulation of large power grid.